Râgıb Paşa-Zâde Lutfî'nin Divânı - Tanrıkulu, Mustafa (My University, 2020)
Râgıbpaşa-zâde Lutfî’nin Divânı isimli bu çalışma, Mehmed Emin Lutfî Bey’in Divân’ının transkripsiyonlu metni ve kapsamlı incelemesinden oluşmaktadır. Bu çalışmaya konu Divân İBB Atatürk Kitaplığı Belediye Yazmaları bölümünde O.53 numarasıyla kayıtlıdır ve bu eserin bilinen tek nüshasıdır. XIX. yy. şairlerinden olan Lutfî’nin doğum ve ölüm tarihleri bilinmemektedir. Şamlı Râgıb Mehmed Paşa’nın oğludur. Bazı memuriyetleri hakkında arşiv belgelerinde bilgiler mevcut ise de bunlar kısıtlıdır. Nakşi – Hâlidî mensubu olduğu şiirlerindenn anlaşılmaktadır. Bu çalışmada Lutfî’nin hayatı ve ailesi, edebi kişiliği ile ilgili değerlendirmeler, Divân’ının şekil ve muhteva açısından incelemesi

The work titled the Divân of Râgıbpaşa-zâde Lutfî consists of a transcribed text and an extensive analysis of Mehmed Emin Lutfî Bey's Divân. Being the subject of the study, Divân is a registered work in İBB Atatürk Library Municipal Manuscripts with the number O.53 and is the only known copy of this work.The birth and death dates of Lutfî, one of the 19th century poets, are unknown. He is the son of Şamlı Râgıb Mehmed Pasha. While there is information in some archives about his job, the information is limited. It is understood from his poems that he was a follower of Nakşi –Hâlidî.The study constitutes Lutfî's life and family, his evaluations about his literary personality, his examination of the Divân in terms of form and content and the transcribed text of Divân.
Keywords: divân; Emin Lutfî; History; Islam; Islamic literature, Turkish; İslam; İslam edebiyatı, Türk; poem; şiir Emin Lutfî; Tarih